Public Health Strategies for Mitigating the Spread of Infectious Diseases in Rural Communities - Putri, Intan Diana; Yuniati, Yuniati; Asriwati, Asriwati (ScieClouds Publishing, 2025)
A research investigation evaluates public health strategies along with their ability to stop infectious diseases from spreading in rural populations. This study measured disease incidence through a quantitative research design focused on evaluating how health education combined with vaccination coverage alongside sanitation access and vector control methods affect disease transmission. The researchers collected their data through surveys which they analyzed by describing it statistically along with applying inference through regression analysis. Health education showed clear effectiveness in cutting down the occurrence of respiratory infections together with diarrheal diseases and vector-borne diseases. The level of vaccination preparedness demonstrated a powerful inverse link to the occurrence rates of disease prevention cases along with malaria and additional vector spread illnesses. The study confirmed access to sanitation facilities as the main factor for cutting down waterborne disease occurrences but also proved how vector control strategies like insecticide-treated nets played an essential role in fighting malaria and dengue infections. Empirical evidence demonstrates that rural areas benefit from combined public health interventions because this research fills gaps in scientific knowledge about these strategies in rural regions. The research demonstrates why rural communities should use multiple integrated strategies to combat their heavy infectious disease load. Research conclusions demonstrate an acute need for policymakers with public health practitioners to implement these interventions which will lead to better health results in underserved populations.